1997
DOI: 10.1021/es9605883
|View full text |Cite
|
Sign up to set email alerts
|

Electrodialytic Remediation of Soil Polluted with Copper from Wood Preservation Industry

Abstract: Electrodialytic soil remediation is a newly developed method for removal of heavy metal from polluted soil. The method is based on a combination of the electrokinetic movement of ions in soil with the principle of electrodialysis. The principle was tested in six experiments using laboratory cells on a copper-polluted Danish loamy sand. The duration of the experiments was varied, and the development of concentration profiles in the soil after the remediation was investigated for two different dc currents (0.1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(82 citation statements)
references
References 8 publications
2
76
0
4
Order By: Relevance
“…The method was first developed for removal of heavy metals from soils [14]. The principle is illustrated in Fig.…”
Section: Electrodialytic Remediationmentioning
confidence: 99%
See 1 more Smart Citation
“…The method was first developed for removal of heavy metals from soils [14]. The principle is illustrated in Fig.…”
Section: Electrodialytic Remediationmentioning
confidence: 99%
“…1) as stationary and water saturated [14]. Later it was shown that for treatment of fine-grained materials as fly ashes and harbour sediment it is beneficial to treat a stirred suspension instead [3,15].…”
Section: Electrodialytic Remediationmentioning
confidence: 99%
“…In connection with remediation of soil, fly ash and wood, anion and cation exchange membranes have been used to separate the material to be remediated and the electrodes, to avoid entering the pH changes into the material and thereby also to optimize the remediation process (Ottosen et al [6]). Due to the special geometry of church vaults and the need to reduce maintenance new electrode units were developed especially for the use of salt extraction from church vaults.…”
Section: The Historical Origin Of the Murals And Their Foundationmentioning
confidence: 99%
“…La remediación electroquímica es una técnica innovadora que puede utilizarse como tratamiento efectivo para la separación de metales contenidos en el estéril de carbón, mediante la aplicación de un campo eléctrico. De la misma manera como los contaminantes metálicos se han eliminado, con buenos resultados, de suelos, cenizas de carbón y sedimentos [4][5][6][7][8][9]. La remediación electrocinética esencialmente involucra la instalación de electrodos y la aplicación de una corriente directa continua, o de un gradiente de potencial a través de éstos, durante cierto tiempo [1].…”
Section: Introductionunclassified